Strategy of Implementing Quantum Method of Tandur Type in Learning Indonesian Language - Zahra, Alifarose Syahda (International Journal on Advanced Science, Education, and Religion, 2024)
This research is motivated by the low achievement of students' grades in learning Indonesian Language courses at UIN Sayyid Ali Rahmatullah Tulungagung. The low student grades indicate the need for a new method in effective learning of Indonesian Language courses given to students. The new learning method that has begun to be applied is the application of the quantum tandur method with the result of increasing the achievement of learning grades for each student. This research focuses on the quantum tandur type learning strategy applied in Indonesian Language courses. The purpose of this research is to determine the effectiveness of the quantum tandur method if applied in teaching Indonesian Language courses. This research uses a classroom action method through four stages: planning, action, observation, and reflection. The main data sources are Lecturers and Students. Based on the results of the study, it can be concluded that the media and strategies in learning methods have a major influence on student learning outcomes.